ANALISIS KETEBALAN DAN SISA UMUR PAKAI PADA PIPA PENYALUR AIR RADIATOR MENUJU KE ENGINE DI PLTMG AMBON PEAKER 30 MW - Hyzkia Away; Edison Effendy; Eka R.A.P. Lilipaly (Journal Mechanical Engineering, 2024)
Ambon Peaker 30 MW. These pipes are prone to corrosion, especially if not protected by a coating, which leads to thickness reduction and shortens the operational lifespan of the pipes. The thickness measurement will be carried out using an Ultrasonic thickness gauge to determine the corrosion rate and the remaining life of the pipe. The standards referenced in data collection are the American Petroleum Institute (API) 570 and the American Society of Mechanical Engineers (ASME) B31.4. The research will be conducted by the author from August 28, 2024, to August 30, 2024, at PLTMG Ambon Peaker 30 MW, Salahutu District, Central Maluku Regency, Maluku Province. The research results show that the minimum thickness reduction indicates a corrosion rate of 0.228 mm/year at Thickness Measurement Location (TML) 17 and 18, while the maximum thickness reduction shows a corrosion rate of 0.564 mm/year at Thickness Measurement Location (TML) 3. Pipes with lower corrosion rates have a remaining life of 5.4 years, while pipes with higher corrosion rates have a remaining life of up to 31.9 years. In conclusion, coating protection is essential to reduce the corrosion rate and extend the service life of the pipes. Keywords: Pipe thickness, Corrosion rate, Pipe remaining life, Ultrasonic thickness gauge.